UNDERSTANDING DIGITAL SKILL DIGITAL NATIVE GENERATIONS THROUGH KPOP FANS - Citra Rosalyn Anwar; Arnidah Arnidah; Amir Amir (International Conference on Social and Islamic Studies, 2021)
This study is based on a research of K-Pop fans' digital skills. These digital skills are very important as the basic foundation in the four pillars of digital literacy which are digital skills, digital ethics, digital culture and digital safety. These digital skills are very important for young K-Pop fans to have because they have a lot of activity and time on the Internet. This makes them vulnerable to various crimes on the internet or known as cybercrimes. This research is a research using case study analysis, by conducting a literature study accompanied by interviews and observations of young KPoP fans in Makassar. The results of this study found that young Kpop fans have good digital skills, even though they are not aware of it as a digital form. This is owned by KPop fans as part of their competence in carrying out various activities on the internet. These digital skills include the ability to access, sorting information sources, using social media and conversation applications, and using digital wallets.